Comparative evaluation of hepatotoxic and nephrotoxic effects of aroclors 1221 and 1254 in female rats - Kutlu, Selim; Colakoglu, Neriman; Halifeglu, Ihsan; Sandal, Suleyman; Seyran, Ayse D.; Aydin, Mehmet; Yilmaz, Bayram (Wiley, 2007)
Polychlorinated biphenyls (PCBs) are persistent environmental pollutants. This study compared effects of two PCB mixtures, Aroclors 1221 (A1221) and 1254 (A1254) on serum levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), urea, creatinine and uric acid in female rats. Histopathological changes in the liver and kidney were also examined. A group of adult Wistar rats served as controls. Groups II and III were subcutaneously injected with A 1221 and A 1254 at 10 mg/kg every other day for 6 weeks. At the end of this period, all animals were decapitated and blood samples were collected. Serum urea, creatinine, uric acid, ALT, AST and ALP levels were determined. Liver and kidney were collected for histopathological examination. They were fixed in formaldehyde and processed for light microscopy. Both A 1221 and 1254 significantly elevated serum ALT (p > 0.05) and AST (p < 0.01) levels compared to the control group. Serum ALP values were significantly increased by A1221 (p < 0.05), but they were unaffected in the A1254 group. Treatment with both A1221 and A 1254 significantly increased serum levels of urea (p < 0.05), creatinine (P < 0.01) and uric acid (except in the A 1221 group; p < 0.005). Distinct histopathological changes including renal corpuscular atrophy, peritubular vascular congestion and dilated cortical tubules, sinusoidal dilatation, congestion and mononuclear cell infiltration were observed. These findings suggest that PCBs may cause nephrotoxicity and hepatotoxicity in female rats. Copyright (c) 2005 John Wiley & Sons, Ltd.
Keywords: PCBs; ALT; AST; ALP; urea; creatinine; uric acid